Catheter Directed Thrombolysis pada Trombosis Vena Dalam Iliofemoral - Fadhil P. Apriansyah; Suko Adiarto (The Indonesian Heart Association, 2014)
Background Iliofemoral deep vein thrombosis (IFDVT) is associated with more severe outflow obstruction which results in more severe DVT symptoms and late clinical sequelae. Despite anticoagulation therapy, IFDVT patients is still at risk to develop postthrombotic syndrome (PTS). Recent studies found that additional catheter-directed thrombolytic therapy may offer advantages in reducing PTS and maintaining venous patency. Several ongoing multi-center randomized controlled trials are expected to evaluate safety and efficacy of CDT in IFDVT patients, and define who will benefit most.Case Illustration A 59-year-old male was presented with numbness, pain, and movement limitation in the left leg that were preceded by left leg swelling. Peripheral edema was found in both patient’s leg but more prominent on the left side. Dupplex sonography revealed extensive soft thrombus from left iliac vein to left tibialis vein. Initial anticoagulation therapy took no effect to the thrombus. Catheter-directed thrombolysis was performed and provided satisfactory symptoms resolution as well as thrombus dissolution.Summary A case of iliofemoral DVT has been reported. The present therapeutic strategy of anticoagulation therapy has not been proven to prevent PTS. CDT is an effective way in achieving clot lysis in acute thrombosis, and this may help to prevent PTS and subsequent ulceration. The potential benefits of therapy must be weighed carefully against the risk of bleeding. There are several ongoing RCTs that are awaited to help provide evidence on functional outcome after CDT and define who will benefit most.